The Effect of Thesaurus Application on Students’ Writing Ability of Recount Text at SMAN 3 Palangka Raya - Indina, Gina Yati; Karani, Elanneri; Retsi, Olga Dona (English Language Education, Universitas Internasional Batam, 2023)
English is an international language that all school levels make it one of the subjects in their school program. Many students still faced difficulties in writing recount text such as they do not know how to make a good sentence and lack of vocabularies. This research was conducted to find out the effect of Thesaurus application on students’ writing ability of recount text at the tenth grade students of SMAN 3 Palangka Raya. The method used in this research was a pre-experimental research. The sample was taken by Purposive Sampling technique from class of X MIPA 3, tenth-grade students of SMAN 3 Palangka Raya in the academic year 2022/2023. Test in form of writing recount text was used as the instrument to collect the data needed. The data of test were analyzed by using the non-parametric statistics of the Wilcoxon test. The results showed that Sig (2-tailed) higher than 0.005 (0.406 > 0.005). It means that the alternative hypothesis (Ha) was rejected and the null hypothesis (Ho) was accepted. It can be concluded that there is no significant effect of Thesaurus application on students’ writing ability at the tenth-grade students of SMAN 3 Palangka Raya in the academic year 2022/2023.